FRI0065 CLINICAL FEATURES OF METHOTREXATE ASSOCIATED LYMPHOPROLIFERATIVE DISORDER IN RHEUMATOID ARTHRITIS PATIENTS AND INFLUENCE OF CD8 POSITIVE LYMPHOCYTE INFILTRATION. (2nd June 2020) - Kameda, T.; Nakashima, S.; Inoo, M.; Onishi, I.; Kurata, N.; Shimada, H.; Mahmoud Fahmy Mansour, M.; Wakiya, R.; Kato, M.; Ushio, Y.; Sugihara, K.; Miyagi, T.; et al.
Abstract : Background: Lymphoproliferative disorders (LPD) that develop in rheumatoid arthritis (RA) patients treated with MTX (MTX-LPD) is one of the important complications for RA patients. We have previously epidemiologically demonstrated an association between MTX and the development of LPD in RA patients 1) . MTX-LPD has varied pathologies including various clinical symptom and histological finding. Therefore, we need more information about MTX-LPD. In addition, it is one of the characteristics for MTX-LPD that spontaneous regression (SR) after MTX discontinuation. However, the mechanism of SR is not clarified. Objectives: We collect the information such as clinical symptom and histological finding of MTX-LPD with RA patients, and clarify the clinical features of MTX-LPD. In addition, we investigated the difference between SR cases and cases that treated with chemotherapy after MTX discontinuation (CTx cases). Methods: We enrolled 90 MTX-LPD patients from Kagawa Prefecture, Japan between June 2005 and December 2019. Patients were diagnosed according to American College of Rheumatology (ACR) 1987 classification criteria or ACR/European League Against Rheumatism (EULAR) 2010 classification criteria, and treated with disease modifying antirheumatic drugs (DMARDs) including MTX. We collected as follow information; age, gender, duration of RA, laboratory data (lymphocyte counts and sIL-2R) and treatment of MTX-LPD. In addition, we divided 16 MTX-LPD cases diagnosed histological into two groups (SR:CTx group; n=10:6), and analyzed the histological findings (CD4, CD8, CD163 and CD47) using the staining in immunohistochemistry (IHC) between the two groups. Each positive cell analyzed using virtual viewer soft ImageScope. Results: Characteristics of 90 MTX-LPD patients are as follow; mean age 66.5±11.2 years, 63 female, duration of RA 18.5±19.4 years. 65 patients (72.2%) were spontaneously improved by discontinuing MTX. 58 patients (64.4%) were proven MTX-LPD histologically. In these patients, diffuse large B-cell lymphoma (DLBCL) was the most frequent histological type of MTX-LPD (56.9%). Infiltration of CD8 positive lymphocyte in the lesion was significant less in the SR cases than in the CTx cases (Figure 1 ). However, CD4, CD163 and CD47 positive cells had no significant difference between two groups. Conclusion: We revealed clinical features of MTX-LPD with RA patients. In addition, CD8 positive lymphocytes are involved in tumor immunity. In this study, we suggested that the extent of CD8 positive lymphocyte infiltration may predict SR of MTX-LPD. Further study is necessary on revealing the mechanism of SR in MTX-LPD. References: [1]Kameda T. et al. Arthritis Care Res (Hoboken). 2014 Sep;66(9):1302-9. Disclosure of Interests: None declared